Genetic gain in agronomic traits of common bean in the region of Planalto Catarinense - Bertoldo J.G. (2010)
The purpose of this study was to predict the genetic progress in the selection for common bean agronomic traits based on the trait expression, using two indices of adaptive selection. The existence of correlation between various traits in common bean breeding is a major restriction, but some tools that allow breeders to predict the expected gains could optimize results. The following traits were evaluated: (1) plant cycle (days), (2) plant height (in cm), (3) stem diameter (cm), (4) insertion of the first pod (cm); (5) number of pods per plant; (6) number of grains per pod; (7) pod length (cm). Results show the possibility of selecting accessions for several agronomically important traits evaluated together. The only genotype selected by both indices was UDESC 03, confirming the possibility of selecting plants with superior agronomic traits among genotypes of common bean landraces. © Springer Science+Business Media B.V. 2009.